2019
DOI: 10.24263/2304-974x-2019-8-3-14
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the effect of calcium chloride on sodium alginate on the restructuring of fish products

Abstract: Introduction. The purpose of this publication is to investigate the mechanism of the restructuring of fishery products using calcium chloride and sodium alginate.Materials and methods. Minced fish fillet of carp (protein -16.5±0.2%; fats -1.2±0.03 %, minerals -1.3±0.03 %); structure-forming agents are sodium alginate, calcium chloride (CaCl2). The method of rotational viscometryrheological characteristics; the method of energy absorption in the mid-wavelength range of the infrared spectrumenergy substances; sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This aggregation results in increased turbidity, higher transition temperatures, reduced surface hydrophobicity of the myosin SAL solution, and the formation of a heterogeneous network with large holes to encase the water. It's important to point out that there will be a decrease in the sensory qualities and rigidity of the meat products due to the high concentration of alginate in the product [125].…”
Section: Alginatementioning
confidence: 99%
“…This aggregation results in increased turbidity, higher transition temperatures, reduced surface hydrophobicity of the myosin SAL solution, and the formation of a heterogeneous network with large holes to encase the water. It's important to point out that there will be a decrease in the sensory qualities and rigidity of the meat products due to the high concentration of alginate in the product [125].…”
Section: Alginatementioning
confidence: 99%
“…Choosing SA as a gelling agent can achieve a lot of advantages, especially its highly regulable ionotropic gelation processes and relatively low costs [ 84 , 85 ]. Nykyforov et al [ 86 ] found that restructured fish products obtained the maximum value of sensory evaluation with a 2-2.5% addition of SA plus a 5% concentration of calcium chloride in the solution. It also reported that adding no less than 3% SA could achieve sufficient gelation of minced meat [ 87 ].…”
Section: Chemical Restructuring Techniquesmentioning
confidence: 99%